Every cloud has a silver lining: The experience of online learning in English language classes at Saudi universities in the post–COVID-19 era - Alqahtani, Muneer Hezam (Frontiers in Education, 2022)
This study investigates the perceptions and attitudes of 149 English language students on online language learning at a state university in Saudi Arabia. It explores how they have experienced online learning during the pandemic and how this experience has prepared them to continue online learning after the pandemic is over. It also investigates whether there have been any differences between the four skills of reading, listening, writing and speaking when it comes to learning them online. The study concludes that, overall, the students have positive attitudes towards learning English online whether during the pandemic or after it is over. However, their views differed when it comes to acquire the four language skills in which learning the receptive skills of reading and listening online was perceived positively whilst learning the productive skills of writing and speaking online was perceived negatively. The study concludes that more advanced technical features are needed to be introduced to online learning platforms for more effective learning outcome and that the current platforms at universities fall a little short of what English language students need.